Integrating MEditatioN inTO heaRt disease (The MENTOR study): Phase II randomised controlled feasibility study protocol. Issue 3 (June 2022) - Rao, Angela; DiGiacomo, Michelle; Phillips, Jane L.; Newton, Phillip J.; Zecchin, Robert; Denniss, Alan Robert; Hickman, Louise D.
Abstract: Background: Additional support services are required to identify and manage poor psychological health symptoms in one in five patients who attend cardiac rehabilitation programs. Meditation has been identified as a low-cost accessible adjunct to conventional therapies and has demonstrated a potential benefit to reducing cardiovascular risk. Aim: This protocol reports on the design and methods of a study that aims to determine the feasibility, acceptability and preliminary efficacy of integrating a meditation intervention into an existing cardiac rehabilitation program for the reduction of depression and anxiety symptoms in people with cardiovascular disease. Methods: This is a mixed methods phase II randomised controlled feasibility pilot study. Sixty patients will be randomised to meditation (1 session weekly for six weeks) and usual cardiac rehabilitation (6 week/12 session outpatient cardiac rehabilitation) or to usual cardiac rehabilitation. Measurements will be conducted at baseline, 6 weeks and 3 months. Preliminary outcomes include feasibility and acceptability of meditation (recruitment, screening, randomisation and attrition rates), and depression, anxiety, stress, salivary cortisol, blood pressure and heart rate outcomes. Participants will be invited to attend a semistructured interview at 6 weeks to explore their experiences of participating in meditation. Health professionals will also be interviewed to ascertain their perspectives of integrating meditation into cardiovascular secondary prevention programs. Discussion: This study will provide preliminary understanding of the feasibility acceptability and preliminary efficacy of meditation as an adjunct therapy for people who may require additional psychological health support. These results may also highlight signals of improvement in psychological health symptoms and inform the development of a future phase III randomised controlled trial.